Вилучення тексту з інтернету на основі навчання машин - Кривенко, С. А.; Шалатов, В. О. (ХНУРЕ, 2023)
In this work, Beautiful Soup is used to extract the titles, authors, summaries, published data, and hyperlinks from blog posts. The extracted text could then be used in a downstream NLP task, such as topic extraction, sentiment analysis, text-to-speech, or translation.
Keywords: NLP; hyperlinks; topic extraction; text-to-speech